Capital Regulation and Risk-taking Behavior: Empirical Evidence for Islamic Banks - Daoud, Yomna; Kammoun, Aida (International Review of Management and Marketing, 2022)
This paper investigates whether regulatory pressures have an impact on the relationship between change in capital and bank risk-taking. On the basis of a well developed theoretical background, capital regulation constitutes the core of prudential regulation within the banking sector. Several researches have investigated this relationship between capital and risk in conventional banks, and this subject has gained in interest since the last financial crisis. This study is one of the few studies that have attempted to provide empirical evidence on this issue for Islamic banks. We use data of Islamic banking sectors over the period 2010–2014. The results reveal that Islamic banks tend to behave differently at each level of capital adequacy. In addition, we provide some evidence that change in capital is positively related to the change in risk for highly capitalized Islamic banks.